Efficient and cost-effective differentiation of induced neural crest cells from induced pluripotent stem cells using laminin 211 - Kazuma Takahashi; Shizuka Aritomi; Fumie Honkawa; Sayaka Asari; Ken Hirose; Atsushi Konishi (Regenerative Therapy)
Introduction: Neural crest cells (NCCs) are cell populations that originate during the formation of neural crest in developmental stages. They are characterized by their multipotency, self-renewal and migration potential. Given their ability to differentiate into various types of cells such as neurons and Schwann cells, NCCs hold promise for cell therapy applications. The conventional method for obtaining NCCs involves inducing them from stem cells like induced pluripotent stem cells (iPSCs), followed by a long-term passage or purification using fluorescence-activated cell sorting (FACS). Although FACS allows high purity induced neural crest cells (iNCCs) to be obtained quickly, it is complex and costly. Therefore, there is a need for a simpler, cost-effective and less time-consuming method for cell therapy application. Methods: To select differentiated iNCCs from heterogeneous cell populations quickly without using FACS, we adopted the use of scaffold material full-length laminin 211 (LN211), a recombinant, xeno-free protein suitable for cell therapy. After fist passage on LN211, iNCCs characterization was performed using polymerase chain reaction and flow cytometry. Additionally, proliferation and multipotency to various cells were evaluated. Result: The iNCCs obtained using our new method expressed cranial NCC- related genes and exhibited stable proliferation ability for at least 57 days, while maintaining high expression level of the NCCs marker CD271. They demonstrated differentiation ability into several cell types: neurons, astrocytes, melanocytes, smooth muscle cells, osteoblasts, adipocytes and chondrocytes. Furthermore, they could be induced to differentiate into induced mesenchymal stem cells (iMSCs) which retain the essential functions of somatic MSCs. Conclusion: In this study, we have developed novel method for obtaining high purity iNCCs differentiated from iPSCs in a short time using LN211 under xeno-free condition. Compared with traditional methods, like FACS or long-term passage, this approach enables the acquisition of a large amount of cells at a lower cost and labor, and it is expected to contribute to stable supply of large scale iNCCs for future cell therapy applications.